The Omnibus Law in the Perspective of Responsive Law and its Impact on Indonesia's Economy - Renaldy Eka Putra (Fakultas Hukum Universitas Lampung, 2021)
The government passed the Job Creation Law using the Omnibus Law concept, to be used to build the Indonesian economy to attract investors to invest in Indonesia. The Job Creation Law has several clusters in it, one of which regulates employment. Therefore this paper aims to analyze in-depth the ratification of the Omnibus Law policy using a responsive legal approach (Based on Law No.12 of 2011 concerning the Formation of Laws and Regulations) and looking empirically at the obstacles in creating employment in Indonesia, the correlation between the Job Creation Law and the principle of justice in the era of the Covid-19 pandemic. The method used in this paper is normative-juridical with a statute approach and a conceptual approach, then content analysis, which describes and analyzes the scope of legal theory. This paper's type of data is secondary data obtained from literature, books, journals and articles, official reports of National Media related to Omnibus Law in Indonesia.